TFCP2 Overcomes Senescence by Cooperating With SREBP2 to Activate Cholesterol Synthesis in Pancreatic Cancer - Zhang, Dexiang; Lu, Pinxiang; Zhu, Kaihua; Wu, Haixia; Dai, Yuedi (Frontiers in Oncology, 2021)
KRAS mutation is very common in pancreatic cancer. How pancreatic cancer cells overcome oncogene-induced aging is not fully understood at present. In our previous studies, we found that expression of transcription factor TFCP2 was upregulated in pancreatic cancer, and promoting the growth and metastasis of pancreatic cancer cells. However, whether TFCP2 plays an important role in pancreatic cancer cell senescence is not clear. In this study, we found upregulation of TFCP2 expression in pancreatic cancer specimens and mouse tissues with KRAS mutation. Overexpression of TFCP2 inhibited cell senescence. Interference with the expression of TFCP2 promoted cell senescence. In the study of the molecular mechanism, we found that interaction between TFCP2 and SREBP2 synergistically activated the expression of HMGCR, a key enzyme in cholesterol synthesis, and that statins could reverse the inhibitory effect of TFCP2 on senescence. In conclusion, our study reveals a new mechanism underlying the TFCP2 regulation of pancreatic cancer cell senescence, providing a new target for the treatment of pancreatic cancer.